2019
DOI: 10.1002/suco.201900012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of jute fiber‐reinforced high‐strength concrete

Abstract: High-strength concrete often suffers from brittleness, so the addition of fibers is an effective way to improve its performance. In this study, jute plant fiber was added to high-strength concrete, and the application method, content, and influence on the mechanical properties were explored. An orthogonal test was used alongside physical and mechanical analyses to test the compressive and tensile strength of 28-day-old jute fiber-reinforced concrete specimens, and the optimum length and content ratio of jute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In addition, the jute fiber can also be utilized in high-strength concrete as a spalling prevention agent [44]. The reinforcement of concrete with jute fibers not only impedes the crack instigation but also helps in post-cracking propagation [45].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the jute fiber can also be utilized in high-strength concrete as a spalling prevention agent [44]. The reinforcement of concrete with jute fibers not only impedes the crack instigation but also helps in post-cracking propagation [45].…”
Section: Introductionmentioning
confidence: 99%
“…Due to increased friction and stronger bonding with the cement slurry, this deepened the grooves on the fiber surface. 45…”
Section: Treatmentsmentioning
confidence: 99%
“…43 Several studies imply that jute fibers can be considered a proper replacement for the traditional fibers in concrete materials. 44 46…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tan et al [8], the ultimate load of concrete columns has been increased by wrapping with JFRP composites. Alam and Al Riyami [9] showed that the toughness and strength of beams have been improved by the reinforcement using the natural fibers [10,11]. On the other hand, the maximum load capacity, ductility, and energy absorption have been increased by using the flax fiber-reinforced polymers (FFRP) [12].…”
Section: Introductionmentioning
confidence: 99%